Comparative efficacies of ofloxacin, cefotaxime, and doxycycline for treatment of experimental epididymitis due to Escherichia coli in rats. - Vieler, E (1993)
The in vivo efficacy of ofloxacin was compared with those of cefotaxime and doxycycline in a rat model of epididymitis due to Escherichia coli. Treatment was started 24 h after infection and was continued for 7 days. Ofloxacin reduced the numbers of E. coli organisms in the epididymides significantly more than the other therapeutic regimens and cured the infection more frequently. Histopathological changes in the epididymides of ofloxacin-treated animals were significantly less severe than those observed in untreated animals. Doxycycline was less effective than ofloxacin but significantly reduced the titers of organisms in rat epididymides. In contrast, despite excellent in vitro activity, cefotaxime failed to reduce the magnitude of infection. The results of this study suggest that ofloxacin may be a very effective antimicrobial agent for the treatment of epididymitis due to E. coli.